Math and gender: Is math a route to a high-powered career? - Juanna Schrøter Joensen; Helena Skyt Nielsen (Institute for the Study of Labor (IZA), 2013)
There is a large gender gap in advanced math coursework in high school that many believe exists because girls are discouraged from taking math courses. In this paper, we exploit an institutional change that reduced the costs of acquiring advanced high school math to determine if access is, in fact, the mechanism - in particular for girls at the top of the math ability distribution. By estimating marginal treatment effects of acquiring advanced math qualifications, we document substantial beneficial wage effects from encouraging even more females to opt for these qualifications. Our analysis suggests that the beneficial effect comes from accelerating graduation and attracting females to high-paid or traditionally male-dominated career tracks and to CEO positions. Our results may be reconciled with experimental and empirical evidence suggesting there is a pool of unexploited math talent among high ability girls that may be retrieved by changing the institutional set-up of math teaching.
Keywords: I21; J24; 330; math; gender; career choice; high school curriculum; instrumental variable